20x-6=2x-12

Simple and best practice solution for 20x-6=2x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20x-6=2x-12 equation:


Simplifying
20x + -6 = 2x + -12

Reorder the terms:
-6 + 20x = 2x + -12

Reorder the terms:
-6 + 20x = -12 + 2x

Solving
-6 + 20x = -12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-6 + 20x + -2x = -12 + 2x + -2x

Combine like terms: 20x + -2x = 18x
-6 + 18x = -12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-6 + 18x = -12 + 0
-6 + 18x = -12

Add '6' to each side of the equation.
-6 + 6 + 18x = -12 + 6

Combine like terms: -6 + 6 = 0
0 + 18x = -12 + 6
18x = -12 + 6

Combine like terms: -12 + 6 = -6
18x = -6

Divide each side by '18'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 16*1500= | | -3x+2=5x+16 | | N/12=12/16 | | 5.88=3(x-.75) | | 7x+10=6x-4 | | x-26=4x+1 | | (-2t^5/at^2)^4 | | 4a+5a=3(1-2a)+6(3a+3) | | 18+13n=5 | | 8-(3-8x)=4x+2 | | 16x+32=90 | | 8(-3.7)= | | 5x-3(x-2)=-7+4x-3 | | 13=-6+k | | 6x-4=-x | | -53+12x=3x+100 | | 16t^2-90t+90=0 | | 4-3y=3-4y | | 5b+8-6b= | | 3x-5/3=96 | | 100=(4*w)*w | | 41790=5(210t) | | 100=(4xw)xw | | -n-21=8-3(n+7) | | 8x-10=7x+2 | | 13-4=x | | x^2-3=a | | ((-5)*c)+(8*c)= | | 2a-8=4(3a+1)-7 | | 2x-19=3x | | -7a+8b=25 | | x^2+.4+3=0 |

Equations solver categories